Analysis Of Aceh Bnnp’s Communication Strategy As Strengthening The P4gn Program From A Maqashid Sharia Perspective - Ananda, Fadhillah; Arifin Melayu, Hasnul; Afrian Mustaqim, Riza (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2025)
The problem of narcotics abuse and illicit trafficking is one of the most serious problems and continues to grab the attention of the community. In carrying out its duties, BNN requires the support and active role of all components of society, which when viewed more deeply in the Law, the community can support the implementation of BNN's duties, one of which is by becoming a P4GN activist. The abuse and illicit trafficking of narcotics and narcotics precursors (P4GN) as mandated in Law Number 35 of 2009 concerning Narcotics in Article 104 explains that "The community has the widest possible opportunity to participate in assisting the prevention and eradication of abuse and illicit trafficking of narcotics and narcotics precursors". This research aims to see how the influence of communication strategies as a means of strengthening the P4GN program, maqashid sharia review of the influence of communication strategies as a means of strengthening the P4GN program. In this study the authors used qualitative research methods with a field research approach. The results of the research obtained are, first, knowing how far the effectiveness of the communication strategy carried out by the Aceh Provincial BNN as a strengthening of the P4GN program and second, knowing how the maqashid sharia review of the strategies used by the Aceh Provincial BNN in terms of realizing the P4GN program.